Different diagnostic criteria influence the determination of Vitamin D nutritional status in children: a cross-sectional study - Qingling Zhu; Qingling Zhu; Yueyuan Zhu; Jiajia Liu; Huiling Huang; Liuhong Huang; Weihua Lin; Weihua Lin (Frontiers in Public Health)
ObjectiveTo assess Vitamin D status in children aged 0–6 years in Quanzhou, China, and compare the impact of diagnostic criteria on deficiency/sufficiency classification.MethodsThis cross-sectional study enrolled 1,183 healthy children aged 0–6 years (January 2022–March 2023). Serum 25(OH)D levels were measured via ELISA, and anthropometric data were collected. Participants were stratified by sex, season, age, WLZ, BMI, and Vitamin A status to analyze Vitamin D variations. Diagnostic criteria impacts on classification were evaluated.ResultsMean serum 25(OH)D was 73.02 nmol/L (IQR: 58.48–89.09), with no sex-based differences (P > 0.05). Levels varied by season (highest in summer: 75.85 nmol/L; lowest in winter: 69.00), and age (infants > toddlers > preschoolers), all P < 0.05. Serum 25(OH)D were observed to decrease with increasing WLZ (Weight-for-Length Z-score) and BMI, though no statistically significant differences were found for either parameter (both P > 0.05) Using Criterion I, 2.46% were deficient, 9.97% insufficient, and 87.57% sufficient (χ2 = 1589.053, P < 0.001). With Criterion II, rates shifted to 12.43, 40.74, and 46.83%, respectively (χ2 = 239.271, P < 0.001). Classification discrepancies were significant across subgroups (sex, season, age, BMI; all P.adj <0.05), with poor inter-criteria agreement (Kappa = 0.071, P < 0.001). Age, season, BMI, and Vitamin A independently predicted sufficiency (P < 0.05).ConclusionThis study underscores two critical implications: (1) Vitamin D deficiency/sufficiency classifications are critically dependent on diagnostic criteria, necessitating region-specific guidelines and standardized threshold selection in practice and research. (2) Given the influence of latitude on Vitamin D synthesis, targeted interventions—particularly increased winter dosing for young children—should be tailored to age and seasonal variations.